Modern Dynamic Engagement Between Sufism and Reiki Meditation - Ary Budianto (ILMU USHULUDDIN, 2012)
Historically and culturally speaking, since the late 1990’s, ‘modern’ Reiki and meditation techniques and practices have impacts on the Indonesian people. The globalization of Reiki on healing attunement that is generated from the Reiki’s meditation technique also has its influences in Islamic traditional wisdom. This Reiki global movement has apparently invoked the traditional syncretistic style of some Indonesian Muslim. In turn, this situation creates political tension between the radical and puritan Islam vis a vis the Muslim Reiki’s masters. Using comparative studies, this paper is based on the current phenomenon of Islam engaged with Reiki and attempts to explore the politics of Reiki as a global product and its relation to the responses within Indonesian Muslim, historically and sociologically, through which we can observe the dynamics dialogue in practice between Buddhism and Islamic Sufism.